2009
DOI: 10.1088/0004-637x/706/1/738
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Bipolar Shell of the Helium Nova V445 Puppis

Abstract: From multi-epoch adaptive optics imaging and integral field unit spectroscopy we report the discovery of an expanding and narrowly confined bipolar shell surrounding the helium nova V445 Puppis (Nova Puppis 2000). An equatorial dust disc obscures the nova remnant, and the outflow is characterised by a large polar outflow velocity of 6720 ± 650 km s −1 and knots moving at even larger velocities of 8450 ± 570 km s −1 . We derive an expansion parallax distance of 8.2 ± 0.5 kpc and deduce a pre-outburst luminosity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(172 citation statements)
references
References 52 publications
6
165
1
Order By: Relevance
“…Wang & Han (2010c) suggested that the hot subdwarf HD 49798 and its X-ray pulsating companion could evolve into an SN Ia in the future. The system V445 Pup is another candidate of a massive WD + He star system, in which the mass of the WD is > ∼ 1.35 M , and the mass of the He star is > ∼ 0.85 M (Kato et al 2008;Woudt et al 2009). …”
Section: Discussion and Summarymentioning
confidence: 99%
“…Wang & Han (2010c) suggested that the hot subdwarf HD 49798 and its X-ray pulsating companion could evolve into an SN Ia in the future. The system V445 Pup is another candidate of a massive WD + He star system, in which the mass of the WD is > ∼ 1.35 M , and the mass of the He star is > ∼ 0.85 M (Kato et al 2008;Woudt et al 2009). …”
Section: Discussion and Summarymentioning
confidence: 99%
“…Some recent examples suggest that bipolarity in the ejecta of classical/recurrent novae may be relatively frequent: RS Oph (Ribeiro et al 2009;Bode et al 2007;Chesneau et al 2007), V445 Pup (Woudt et al 2009), V1280 Sco (Chesneau et al 2008;Chesneau et al, in prep. ) or HR Del (Harman & O'Brien 2003).…”
Section: A Face-on Bipolar Eventmentioning
confidence: 99%
“…Helium overabundance is spectroscopically observed in some recurrent novae, U Sco (Williams et al 1981;Hanes 1985;Starrfield et al 1988) and V394 (Sekiguchi et al 1989), and some classical novae, Nova LMC 1990No. 2 (Sekiguchi et al 1990Shore et al 1991) and V445 Puppis (Nova Puppis 2000; Ashok & Banerjee 2003;Kato & Hachisu 2003;Kato et al 2008;Woudt et al 2009;Goranskij et al 2010). In most considerations in the literature, the helium-rich secondaries are the cores of stars stripped of their red giant envelopes by mass transfer (Iben & Tutukov 1994;Yoon & Langer 2003;Solheim & Yungelson 2005;Ruiter et al 2009Ruiter et al , 2011Wang et al 2009aWang et al , 2009bWang & Han 2009;Meng & Yang 2010).…”
Section: Discussionmentioning
confidence: 99%